2011
DOI: 10.1371/journal.pone.0017516
|View full text |Cite|
|
Sign up to set email alerts
|

Disturbance and the Dynamics of Coral Cover on the Great Barrier Reef (1995–2009)

Abstract: Coral reef ecosystems worldwide are under pressure from chronic and acute stressors that threaten their continued existence. Most obvious among changes to reefs is loss of hard coral cover, but a precise multi-scale estimate of coral cover dynamics for the Great Barrier Reef (GBR) is currently lacking. Monitoring data collected annually from fixed sites at 47 reefs across 1300 km of the GBR indicate that overall regional coral cover was stable (averaging 29% and ranging from 23% to 33% cover across years) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
209
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(217 citation statements)
references
References 54 publications
(82 reference statements)
4
209
4
Order By: Relevance
“…The rate of decline has also increased substantially, and has averaged ∼1.45% y −1 since ∼2006. Both the overall and more recent rates of decline are higher than previous estimates (13,14), which were either based on time series that ended in 2005 (14) or covered a shorter period (1995-2009) and surveyed far fewer reefs using a different survey method (13). The disturbance data for COTS or cyclones show periodic and random fluctuations but no systematic long-term variation over the 27-y observation period, and given that GBR coral cover was likely higher than 28% before 1985 (2), the decline in coral cover may have started long before then.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…The rate of decline has also increased substantially, and has averaged ∼1.45% y −1 since ∼2006. Both the overall and more recent rates of decline are higher than previous estimates (13,14), which were either based on time series that ended in 2005 (14) or covered a shorter period (1995-2009) and surveyed far fewer reefs using a different survey method (13). The disturbance data for COTS or cyclones show periodic and random fluctuations but no systematic long-term variation over the 27-y observation period, and given that GBR coral cover was likely higher than 28% before 1985 (2), the decline in coral cover may have started long before then.…”
Section: Discussioncontrasting
confidence: 69%
“…The recent frequency and intensity of mass coral bleaching are of major concern, and are directly attributable to rising atmospheric greenhouse gases (3). To date, the GBR has lost fewer corals to bleaching and diseases than many other regions in the world (13,24), but bleaching mortality will almost certainly increase in the GBR, given the upward trend in temperatures (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Halford et al [107] found complete recovery of corals and nearly total recovery of �sh assemblages over 80 km of the Great Barrier Reef about a decade aer major storm damage. Monitoring of sites across 1300 km of the Great Barrier Reef (1995 to 2009) indicated increases in coral cover for some reefs but decreases for others [115]. Recently, De'ath et al [9] reported a loss of over 50% coral cover along the Great Barrier Reef from 1985 to 2012 based on surveys of 214 reefs, attributing the decline to cyclones (48%), Crown-of orns star�sh (42%), and bleaching (10%).…”
Section: Where In the World Have Reefs Recovered?mentioning
confidence: 99%